(untitled) (REMUNOM, 2025)
Relevant literature indicates that cervical cancer is currently one of the major public health challenges in Brazil, with invasive squamous cell carcinoma representing the most prevalent histological subtype. Its occurrence is strongly associated with infection by human papillomavirus (HPV), particularly oncogenic subtypes 16 and 18, which are recognized as carrying the highest risk for malignant transformation. This study aims to characterize the epidemiological profile of cervical cancer in Brazil, within the time frame between 2020 and 2024, considering regional distribution, age groups, and the most affected ethnic populations. A quantitative research was conducted using secondary data retrieved from the Cancer Information System (SISCAN/DATASUS). The data were analyzed descriptively and presented through comparative charts. The results indicated a higher concentration of cases in the Southeast and Northeast regions, although relevant proportions were also recorded in the South, North, and Center-West. The most affected age group comprised women between 40 and 64 years, with notable peaks among those aged 55–59 and 60–64. However, an increasing incidence was observed among younger women, particularly those aged 40–44, which may be associated with risk-related sexual behaviors, early onset of sexual activity, and insufficient HPV vaccination coverage. With regard to ethnicity, cases were predominantly identified among white and yellow women, suggesting the influence of social inequalities and disparities in access to health services, early diagnosis, and adequate follow-up. Therefore the study concludes that despite the availability of effective preventive and screening methods, cervical cancer continues to reach significant incidence rates in Brazil. The findings underscore the urgent need to expand vaccination coverage, strengthen screening programs, ensure timely diagnosis, and reduce regional and social disparities. Such measures are essential for the development of more equitable and effective public health policies to address this neoplasm.